2010
DOI: 10.1053/j.ajkd.2010.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive Severe Vascular Calcification Sparing the Kidney Allograft Following Warfarin Initiation

Abstract: We describe a case of rapid onset of vascular calcification coincident with the initiation of warfarin therapy in a kidney transplant patient. Calcification developed within the media of the blood vessel wall, with relative intimal sparing. Medium and small sized arteries were affected, but the aorta was mostly free of calcifications, suggesting a differential response to warfarin between the intima and media as well as between different vascular beds. In addition, unlike the highly calcified native kidney's v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…Koos et al (21) demonstrated that subjects taking anticoagulants had a significantly higher degree of arterial and aortic valve calcification than control subjects. In a case report, Hristova et al (22) described a kidney transplant recipient exhibiting massive arterial calcification after the initiation of warfarin therapy. Distal subcutaneous necrosis ultimately led to the patient's death.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Koos et al (21) demonstrated that subjects taking anticoagulants had a significantly higher degree of arterial and aortic valve calcification than control subjects. In a case report, Hristova et al (22) described a kidney transplant recipient exhibiting massive arterial calcification after the initiation of warfarin therapy. Distal subcutaneous necrosis ultimately led to the patient's death.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…In the majority of adult patients, the rate of vascular calcification slows considerably post-transplantation; however, despite normalization of serum calcium and phosphorus levels, these lesions often do not regress [ 80 , 81 ] (Fig. 1 ), and, in some patients, particularly those treated with warfarin therapy, an accelerated progression of vascular calcifications may even be observed [ 82 ]. EBCT is not used to evaluate vascular calcification in children; however, EBCT data from young adults who developed renal failure as children, as well as autopsy and biopsy data indicate that vascular calcification is present in children with late stages of CKD [ 83 ] and those treated with maintenance dialysis [ 64 , 80 , 84 , 85 ], particularly those treated with high doses of calcium-containing phosphate binders [ 64 ].…”
Section: Cardiovascular Calcificationmentioning
confidence: 99%
“…The first study [35] demonstrating strongly increased calcification of the aortic valves in patients taking oral anticoagulants—including warfarin and acenocoumarol—has been confirmed by many other researchers: Koos et al demonstrated that subjects taking vitamin K antagonist anticoagulants had a significantly higher degree of arterial and aortic valve calcification than control subjects [36]. In a case report, Hristova et al described a kidney transplant recipient exhibiting massive arterial calcification after the initiation of warfarin therapy [37]. Distal subcutaneous necrosis ultimately led to the patient’s death.…”
Section: Anti-vitamin K Treatment and Effects—warfarinmentioning
confidence: 96%